Diagnosing Growth Constraints in Central Asia: The Case of the Kyrgyz Republic. Issue 3 (September 2018) - Sydykova, Meerim; Rodriguez, Carlos
The Kyrgyz Republic is a country with a transitional economy. Its growth performance is constantly one of the lowest compared to the other members of the Commonwealth of Independent States. This weak performance is mainly caused by political instability and high corruption. Despite being a leading reformer in the region, the country has not done enough to solve its key problems. The current study employs the growth diagnostic approach proposed by Hausmann, Rodrik, and Velasco (2005, Growth diagnostics. Cambridge, MA: The John F. Kennedy School of Government, Harvard University) to identify binding constraints on growth. This article finds that weak institutional performance, high corruption, a large share of the informal economy, and an inefficient energy sector are the most binding constraints on the country's growth.